Experience and results with a telehealth treatment program in patients with cognitive disorders during the COVID-19 pandemic - Dorman, Guido (2020)
The COVID‐19 pandemic has led to the adoption of social quarantine measures in numerous countries. In this context, both COVID‐19 and quarantine can have a substantial impact in the mental health of affected populations. Health care services have had to adapt themselves to this new reality.